Republic of Croatia : Selected Issues and Statistical Appendix. (IMF Staff Country Reports; Country Report ;, 2000)
The development of the Croatian financial sector has faced many of the difficulties experienced by other transition countries. Recent troubles have exacted a significant macroeconomic price but the strategy implemented by the Croatian National Bank (CNB) since the approval of the new banking law promises the early resolution of the more immediate problems. GDP at constant prices, trends in total labor costs, price developments, retail inflation rates, agricultural production, consolidated central government fiscal accounts, government employment, health insurance, disability and retirement insurance, and so on are presented in detail.